Nation/Natio: Raymond Williams and “The Culture of Nations” - Prendergast, Christopher (Intermédialités / Intermediality)

(untitled) (Centre de recherche sur l'intermédialité, 2003)
This article invites us to return to the example of Raymond Williams, and his essay “the Culture of Nations” as a then timely — and continuingly relevant — intervention in the debates about nation and postcoloniality. In linking the categories of nation, “natio” and place, Williams attempts to show that — at least in the case of Britain — the identities in question are produced from complex, multiethnic, long-haul histories, irreducible to the superficial discourses of ethnic patriotism. His argument is at once a confrontation with racism and — more controversially — with liberalism, or at least that version of the latter which seeks to oppose the former in the name of purely abstract juridical “rights”.